Symbol of Fertility and Prosperity of the Pasai Ocean Civilization in the Era of Sultanah Nahrasyiah - Ichsan Ichsan (Journal of Humanities Research Sustainability, 2024)
Background. The Samudera Pasai Kingdom was one of the most famous Kingdoms of its time. Its territorial area has now become the government area of North Aceh Regency, Aceh Province. Samudera Pasai was once called the first Islamic Kingdom in the Southeast Asian region. Purpose. This research aims to find out the symbol of fertility and prosperity of the Samudera Pasai Civilization from the tomb of Sultanah Nahrasyiah. Through field observation and data analysis, anthropological methods are used to understand and analyze human behavior and culture. Method. This method involves using various data collection techniques, including interviews, observations, questionnaires, and document analysis, to obtain in-depth information about a group or society's social, cultural, and mindset. Results. The Samudera Pasai Civilization, during the reign of Sultanah Nahrasyiah, displayed rich symbols of fertility and prosperity. These were evident in various motifs found on the Sultanah's tomb, including banana trees, cotton trees, lotus flowers, and chandeliers. These symbols reflect the civilization's cultural values and beliefs regarding abundance and well-being during this significant historical period. Conclusion. The study results show that the symbols of fertility and prosperity are described as banana tree motifs, cotton tree motifs, lotus flower motifs, and chandelier motifs (chandeliers).